2017
DOI: 10.3390/ma10030310
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Studies of Structure Transformation and Al Coordination of KAl(MoO4)2 during Heating by High Temperature Raman and 27Al NMR Spectroscopies

Abstract: Recent interest in optimizing composition and synthesis conditions of functional crystals, and the further exploration of new possible candidates for tunable solid-state lasers, has led to significant research on compounds in this family MIMIII(MVIO4)2 (MI = alkali metal, MIII = Al, In, Sc, Fe, Bi, lanthanide; MVI = Mo, W). The vibrational modes, structure transformation, and Al coordination of crystalline, glassy, and molten states of KAl(MoO4)2 have been investigated by in-situ high temperature Raman scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…This result indicates that the glass became more disordered after fire polishing. The results are supported by the high‐temperature 27 Al NMR method; the Al is presented predominantly in Al Ⅴ and Al Ⅵ units in the melt or glasses quenched from the liquids 35‐38 . The subsequent annealing of the fire‐polished YbAPF0.85 glass led to the narrowing of the spectrum and a slight decrement in the Al Ⅴ units, as shown in Table 4.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…This result indicates that the glass became more disordered after fire polishing. The results are supported by the high‐temperature 27 Al NMR method; the Al is presented predominantly in Al Ⅴ and Al Ⅵ units in the melt or glasses quenched from the liquids 35‐38 . The subsequent annealing of the fire‐polished YbAPF0.85 glass led to the narrowing of the spectrum and a slight decrement in the Al Ⅴ units, as shown in Table 4.…”
Section: Resultssupporting
confidence: 53%
“…The results are supported by the high-temperature 27 Al NMR method; the Al is presented predominantly in Al Ⅴ and Al Ⅵ units in the melt or glasses quenched from the liquids. [35][36][37][38] The subsequent annealing of the fire-polished YbAPF0.85 glass led to the narrowing of the spectrum and a slight decrement in the Al Ⅴ units, as shown in Table 4. Figure 5C shows the 31 P MAS NMR spectra of the investigated glasses.…”
Section: Network Structure Of Glassmentioning
confidence: 95%
“…Luz‐Lima et al studied the low‐temperature cubic and high‐temperature orthorhombic phases of NWO (Na 2 WO 4 ) crystal and further performed mode assignment on the basis of the lattice dynamics calculations of Na 2 MoO 4 . Previous report on the theoretical calculation of Raman active vibrational modes of molybdate showed that the wavenumber simulated by density functional theory (DFT) is more satisfied with experiment than that by lattice dynamics calculations . The vibrational mode of these two phases is therefore revisited by DFT simulation based on NWO itself, and some minor modifications are hence made in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…This cooling allowed for the cleaning of the silica glass prior to measurement. Figure 6, it is clear that the peak position of the D band related to the low molecular weight carbon organics, while the intensity of the D band changed negligibly with the increasing temperature [26,27]. This implies an increase in the graphitization degree along with the increase in temperature.…”
Section: In Situ High-temperature Study Of Different Coals By Ramanmentioning
confidence: 93%